The effect of livestock, altitude and slope on a red-legged partridge population in Alentejo, Portugal - Ramalho, Helena (2011)
Red-legged partridge (Alectoris rufa) is a non-migratory bird found mainly in the Iberian Peninsula whose conservation status is Least Concern. However, in the last decades there has been a growing concern for the loss of habitat quality due to the results of either land abandonment or farming intensification. This study was conducted in an agrosilvopastoral land use system called montado.